US WAR ON TERRORISM AND ITS IMPACT ON SOUTH ASIA - Prof. Dr. Razia Musarrat. (Journal of Political Studies, 2007)
A reading of history gives one the impression that characteristically the gamut of history is divided into different phases, of short and long duration. Each of the numerous phases of history typically starts with the happening of some events of extra ordinary importance, whose profound implications dominate the world stage throughout the phase. The contemporary phase of the history is, beyond doubt, dominated by the phenomenal war on terrorism. The US-led war on terrorism which started in 2001 has been the characteristic feature of the first decade of the new century. Its impact has been as pervasive as common for all the nations of the world and for designs of their interaction with one another. South Asia, on account of a number of factors, has been at the centre stage in this global fight. As a consequence, it has left overwhelmingly impact on the different states in this region. This impact has been not only on the regional dynamics, not only on the bilateral relations of the South Asian states, but also, most significantly, on their domestic politics as well. This paper will make an effort to have a brief assessment of such an impact on all the three levels.